A Change from a Spinal Immobilization to a Spinal Motion Restriction Protocol was Not Associated with an Increase in Disabling Spinal Cord Injuries. Issue 6 (3rd December 2021) - Clemency, Brian M.; Natalzia, Peter; Innes, Johanna; Guarino, Sharon; Welch, Jacob V.; Haghdel, Arsalan; Noyes, Ekaterina; Jordan, Jeffery; Lindstrom, Heather A.; Lerner, E. Brooke
Abstract: Background: Over the past decade, Emergency Medical Service (EMS) systems decreased backboard use as they transition from spinal immobilization (SI) protocols to spinal motion restriction (SMR) protocols. Since this change, no study has examined its effect on the neurologic outcomes of patients with spine injuries. Objectives: The object of this study is to determine if a state-wide protocol change from an SI to an SMR protocol had an effect on the incidence of disabling spinal cord injuries. Methods: This was a retrospective review of patients in a single Level I trauma center before and after a change in spinal injury protocols. A two-step review of the record was used to classify spinal cord injuries as disabling or not disabling. A binary logistic regression was used to determine the effects of protocol, gender, age, level of injury, and mechanism of injury (MOI) on the incidence of significant disability from a spinal cord injury. Results: A total of 549 patients in the SI period and 623 patients in the SMR period were included in the analysis. In the logistic regression, the change from an SI protocol to an SMR protocol did not demonstrate a significant effect on the incidence of disabling spinal injuries (OR: 0.78; 95% CI, 0.44 - 1.36). Conclusion: This study did not demonstrate an increase in disabling spinal cord injuries after a shift from an SI protocol to an SMR protocol. This finding, in addition to existing literature, supports the introduction of SMR protocols and the decreased use of the backboard.